Ethanol‐assisted dispersion of attapulgite and its effect on improving properties of alginate‐based superabsorbent nanocomposite. Issue 3 (23rd November 2012) - Wang, Yizhe; Shi, Xiaoning; Wang, Wenbo; Wang, Aiqin
Abstract The dispersion of attapulgite (APT) as nanorod‐like single crystals is crucial to fully develop its functionality of one‐dimensional nanometer material as a filler of composite materials. In this study, APT was dispersed by the assistance of ethanol during the high‐pressure homogenization process to form individual nanorod‐like crystals. The dispersed APT was used to prepare new sodium alginate‐g‐poly(sodium acrylate‐co‐styrene)/attapulgite (NaAlg‐g‐P(NaA‐co‐St)/APT) superabsorbent nanocomposites. The effect of ethanol/water ratio on the dispersion of crystal bundles of APT was investigated by field emission scanning electron microscopy, and the results indicate that APT crystal bundles were effectively disaggregated in ν(CH3CH2OH) : ν(H2O) − 5 : 5 solution after homogenized at 50 MPa. The better dispersion of APT in NaAlg‐g‐P(NaA‐co‐St) matrix has clearly improved the gel strength (from 1300 Pa to 1410 Pa, ω = 100 rad/s), swelling capacity (442–521 g/g), swelling rate (3.3303–4.5736 g/g/s), and reswelling ability of the superabsorbent nanocomposite. Moreover, the nanocomposites showed fast swelling–deswelling responsive behavior in different saline solutions. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013